Bosutinib efficacy and safety in chronic phase chronic myeloid leukemia after imatinib resistance or intolerance: Minimum 24‐month follow‐up. Issue 7 (28th April 2014) - Gambacorti‐Passerini, Carlo; Brümmendorf, Tim H.; Kim, Dong‐Wook; Turkina, Anna G.; Masszi, Tamas; Assouline, Sarit; Durrant, Simon; Kantarjian, Hagop M.; Khoury, H. Jean; Zaritskey, Andrey; Shen, Zhi‐Xiang; Jin, Jie; et al.
<x xml:space="preserve">Abstract</x> Bosutinib is an orally active, dual Src/Abl tyrosine kinase inhibitor for treatment of chronic myeloid leukemia (CML) following resistance/intolerance to prior therapy. Here, we report the data from the 2‐year follow‐up of a phase 1/2 open‐label study evaluating the efficacy and safety of bosutinib as second‐line therapy in 288 patients with chronic phase CML resistant (n = 200) or intolerant (n = 88) to imatinib. The cumulative response rates to bosutinib were as follows: 85% achieved/maintained complete hematologic response, 59% achieved/maintained major cytogenetic response (including 48% with complete cytogenetic response), and 35% achieved major molecular response. Responses were durable, with 2‐year estimates of retaining response >70%. Two‐year probabilities of progression‐free survival and overall survival were 81% and 91%, respectively. The most common toxicities were primarily gastrointestinal adverse events (diarrhea [84%], nausea [45%], vomiting [37%]), which were primarily mild to moderate, typically transient, and first occurred early during treatment. Thrombocytopenia was the most common grade 3/4 hematologic laboratory abnormality (24%). Outcomes were generally similar among imatinib‐resistant and imatinib‐intolerant patients and did not differ with age. The longer‐term results of the present analysis confirm that bosutinib is an effective and tolerable second‐line therapy for patients with imatinib‐resistant or imatinib‐intolerant chronic phase CML. ClinicalTrials.gov Identifier: NCT00261846. Am. J. Hematol. 89:732–742, 2014. © 2014 The Authors American Journal of Hematology Published by Wiley Periodicals, Inc.